Perbandingan hasil belajar dan aktivitas siswa dengan menggunakan model pembelajaran Think Talk Write (TTW) dan Numbered Head Together (NHT) pada materi hukum dasar kimia dan perhitungan kimia - Fabella, Yayang; Jasmidi (ARKA INSTITUTE, 2022)
This study aims to the learning outcomes learning activities and a significant correlation beetweenlearning outcomes and student activities thar were taught with the TTW mode assisted and NHT on chemical of basic laws and chemical calculations matter at SMA Negeri 2 Tanjung Morawa. From the result of data analysis obtained for learning outcomes students who are taught with TTW model are higher than NHT . So hypothesis testing is carried out using one sample t test at a significant level of 5 % showing that in learning outcomes tcount more than ttable ttabel. Whereas learning activities that were taught in TTW model are higher than the learning activities NHT. For hypothesis testing showing than in learning activities tcount more than ttable. So there is significant correlation between learning outcomes and student activities taught with TTW model. The results of correlation the two variables are included in the high category.